Enhancing Students’ Achievement in Chemical Equilibrium Through a Scientific Literacy-Integrated 7E Learning Cycle E-Module - Ahmad Maulana Ardi; Desy Kurniawati; Hardeli; Rahadian Zainul; Umar Kalmar Nizar (Jurnal Penelitian Pendidikan IPA, 2025)
Scientific literacy is crucial in chemistry education, yet PISA results indicate that Indonesian students still struggle with abstract concepts like chemical equilibrium. To address this issue, this study developed a scientific literacy-integrated e-module based on the Learning Cycle 7E model to improve student learning outcomes. Using an educational design research approach with the Plomp model, the e-module’s validity, practicality, and effectiveness were evaluated. Validation by subject matter and media experts yielded high validity scores of 0.89 and 0.91, respectively. Practicality testing involving teachers and students resulted in high scores of 91.27% and 89.70%. Effectiveness analysis, measured using the N-Gain formula, showed a significant improvement in students' learning outcomes. These results indicate that the developed e-module is valid, practical, and effective in supporting the understanding of chemical equilibrium among senior high school students.